Evaluating the Role of Project Management Offices (PMOs) in Large-Scale Construction Projects: Insights from Construction Industry Professionals - Umasekar, Vijayakumar (Future Science / FSH-PH Publications, 2024)
This research paper evaluates the role of Project Management Offices (PMOs) in large-scale construction projects, with insights from construction industry professionals. The study's main objective was to bridge the gap in literature by obtaining direct perspectives from those managing these projects. A structured online survey, encompassing both quantitative and qualitative questions, was administered to a diverse group of professionals. The analysis, conducted using statistical software for quantitative data and thematic analysis for qualitative insights, led to several key findings. PMOs were perceived as highly effective in aligning project objectives, resource allocation, process standardization, communication facilitation, and risk management. Notable challenges included resistance to change, inadequate senior management support, resource constraints, and project complexity. PMOs positively impacted project timelines, budget management, stakeholder engagement, and quality of deliverables. High integration of sustainability practices and moderate to high adoption of innovative technologies were also observed. Key success factors for PMOs included effective leadership, clear objectives, skilled teams, robust risk management, and effective stakeholder communication. Over 89% of respondents were satisfied with PMO performance. The study contributes to the existing body of knowledge by providing practical insights and confirming the critical role of PMOs in the success of large-scale construction projects. It highlights the importance of PMOs in driving sustainability and technological advancements, thus offering actionable guidance for enhancing PMO effectiveness in the construction industry.